Comparison of nanomedicine-based chemotherapy, photodynamic therapy and photothermal therapy using reduced graphene oxide for the model system. (9th December 2016) - Liu, Jingjing; Liu, Kai; Feng, Liangzhu; Liu, Zhuang; Xu, Ligeng
Abstract : Because of the efficient heat diffusion, rGO-based photothermal therapy showed better therapeutic efficacy compared to rGO-based chemo- and photodynamic therapies. Abstract : Given the complexity of tumors, several nanomaterial-based treatment modalities like chemotherapy (CT), photodynamic therapy (PDT) and photothermal therapy (PTT) have been developed for combating cancers. However, it is still unclear which strategy is better or how to select optimal approaches for combination treatment since each strategy has been investigated under different conditions. Inspired by its good payload capacity and unique near-infrared absorption, reduced graphene oxide (rGO) was selected in this study as the carrier for loading of doxorubicin (DOX), a chemotherapy drug, and chlorin e6 (Ce6), a photosensitizer. The therapeutic efficacies of PTT, CT and PDT were systematically investigated in vitro using 2D culture and multicellular tumor spheroid (3D) models. Interestingly, while all three types of therapies delivered by rGO appeared to be effective in the conventional 2D cell culture model, only PTT but not CT and PDT showed great treatment efficacy in the 3D tumor spheroid model at the tested concentrations. Such a difference is due to the fact that heat diffusion is much more efficient than the diffusion of therapeutic molecules inside the tumor. Furthermore, in vivo evidence also confirmed the unique advantage of PTT compared to the other two treatment modalities using the TdT-mediated dUTP nick end labeling (TUNEL) staining assay. This study highlights the unique advantages of nanomedicine-based photothermal therapy among these three modalities in cancer treatment in terms of killing tumor cells located far from tumor blood vessels.